Tillering as a trait to mitigate damages caused to maize by the main stem defoliation Perfilhamento como característica mitigadora dos prejuízos ocasionados ao milho pela desfolha do colmo principal - Schmitt A.* (2012)
The objective of this work was to verify if tillers can mitigate damages caused by the main stem defoliation in maize. The experiments were set up in Lages, SC, Brazil, on 10/20/2006 and 10/31/2008. The experimental design was a randomized block with split plots. Two tiller destinations were tested in the main plots: tillers preserved until harvesting, and tillers removed when the main stem had nine expanded leaves (V9). Four main stem defoliation times were assessed in the split plots: V9, V15 (15 expanded leaves), VT (tasseling), and leaf maintenance until harvesting. Hybrid P30F53 was tested at 55 thousand plants per hectare. Total grain yield, tiller grain yield and main stem grain yield were determined. Defoliations performed at V15 and VT decreased total productivity, in comparison to the control, regardless of tiller destination. When the main stem was defoliated at V15 and VT, plots where tillers were kept promoted higher total grain yield than those where tillers were removed. This indicates that tillers were instrumental to maize main stem when there were restrictions to the production of carbohydrates due to leaf area loss close to flowering.